Explanation:
Since g(f(x))=x g ( f ( x ) ) = x , f−1(x)=2x f - 1 ( x ) = 2 x is the inverse of f(x)=12x f ( x ) = 1 2 x .
Replace f(x)f(x) with yy.
y=12xy=12x
Interchange the variables.
x=12yx=12y
Solve for yy.
Rewrite the equation as 12y=x12y=x.
12y=x12y=x
Multiply both sides of the equation by 22.
2⋅12⋅y=2⋅x2⋅12⋅y=2⋅x
Simplify 2⋅12⋅y2⋅12⋅y.
Cancel the common factor of 22.
Cancel the common factor.
2⋅12⋅y=2⋅x2⋅12⋅y=2⋅x
Rewrite the expression.
1⋅y=2⋅x1⋅y=2⋅x
Multiply yy by 11.
y=2⋅xy=2⋅x
Solve for yy and replace with f−1(x)f-1(x).
Replace the yy with f−1(x)f-1(x) to show the final answer.
f−1(x)=2xf-1(x)=2x
Set up the composite result function.
g(f(x))